GOVERNMENT FINANCIAL CONTROL AND ITS IMPACT ON CHECKING THE BUDGET ITEMS: THE IRAQI FINANCIAL BUDGET AS A MODEL (World Economics and Finance Bulletin, 2022)
The research aims to shed light on the nature of government financial control and its relationship to auditing and evaluating balancing items in the Iraqi environment. As well as shedding light on the most important observations in balancing items in the Iraqi environment, which were discovered through government financial control. It was based on a sound scientific and practical basis, and the most important recommendations were reached, resorting to the application of the contractual budget in the Iraqi environment, in addition to balancing the items, as it helps in providing Radical solutions to many problems facing government departments, in particular the elimination of government red tape, poor performance and low quality of services provided to citizens, through the conclusion of service contracts in the operational side of the budget and the reduction of financial and administrative corruption in the implementation of budget items in the Iraqi environment.
Keywords: government financial control; general budget; items budget